Methods of Extracting Useful Components of Plants and their Application in Biological Research (International Journal of Food and Nutritional Sciences, 2022)
Plants and herbs have been used as food and medicine for thousands of years. It is hard to get the bioactive parts of plants out for studies in phytochemistry and biology. Herbalists and scientists have come up with a number of ways to get bioactive constituents out of crude medicines to make sure they work. New plant leads like morphine, quinine, taxol, artemisinin, and alkaloids need careful extraction of active phytochemicals to reduce synthesis and separation costs. Thus, bioactive ingredient-rich extracts and fractions must be extracted from plants using proper procedures. Thus, extraction methods affect yield, phytochemical content, etc. This chapter describes and compares herb and medicinal plant bioactive component extraction methods.